The Role of Teachers in Transforming Islamic Religious Education Values to Enhance Students’ Moral Development at SMP Islam Al-Madinah Jombang - Denmas Amirul Haq; Safi’i, Imam; Afifullah, Muhammad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study aims to examine the role of teachers in transforming the values of Islamic Religious Education (IRE) to enhance students' moral development. The research focuses on: (1) the moral condition of students, (2) the educational values transmitted by teachers, and (3) teacher strategies in shaping students' morality. This research employs a qualitative approach, utilizing observation, interviews, and documentation at SMP Islam Al-Madinah Jombang. The findings show that students exhibit varying but generally positive levels of moral development. Teachers act as educators and role models, transmitting values of faith, honesty, responsibility, tolerance, and social care through value-based learning, exemplary behavior, and the habituation of noble character. These findings affirm that the transformation of values by teachers significantly contributes to students’ character building and fosters a religious school culture. This study offers practical contributions to strengthening teachers’ roles in moral education at the junior high school level. Data collection techniques were employed through direct observation of learning activities at SMP Islam Al-Madinah, Jombang.